2013
DOI: 10.1007/978-3-642-40328-6_19
|View full text |Cite
|
Sign up to set email alerts
|

A Local Computation Approximation Scheme to Maximum Matching

Abstract: We present a polylogarithmic local computation matching algorithm which guarantees a (1−ǫ)-approximation to the maximum matching in graphs of bounded degree.Related work. In the distributed setting, Itai and Israeli [10] showed a randomized algorithm which computes a maximal matching (which is a 1/2-approximation to the maximum matching) and runs in O(log n) time with high probability. This result has been improved several times since (e.g., [4,8]); of particular relevance is the approximation scheme of Lotker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 22 publications
0
37
0
Order By: Relevance
“…This random seed is a costly resource and we try to minimize its length. Known randomised implementations of greedy algorithms in the CentLOCAL domain require explicit random ordering constructions [3,30] over the vertices or edges [3,22,23,30]. In our implementation of the simulation, on the other hand, we use a permutation over the labels, which is a stronger requirement than a random ordering.…”
Section: Noveltymentioning
confidence: 99%
“…This random seed is a costly resource and we try to minimize its length. Known randomised implementations of greedy algorithms in the CentLOCAL domain require explicit random ordering constructions [3,30] over the vertices or edges [3,22,23,30]. In our implementation of the simulation, on the other hand, we use a permutation over the labels, which is a stronger requirement than a random ordering.…”
Section: Noveltymentioning
confidence: 99%
“…Very efficient solutions are known, some of which yield constant factor approximation to maximum matching size in poly(d) time, where d is the maximum degree of the graph (see, e.g. [17,19,4,18,15] and references therein). None of these algorithms, however, seem directly amenable to the streaming model when the underlying graph has unbounded degree.…”
Section: Related Workmentioning
confidence: 99%
“…[MV13], showed that there exists a (1 − ǫ)-approximation algorithm to maximum matching. Unfortunately, that algorithm does not yield a monotonic allocation.…”
Section: Open Questionmentioning
confidence: 99%